Vibration control of FSAE quarter car suspension test rig using magnetorheological damper - Muhammad Adhar Bagus; Azizan As’arry; Hesham Ahmed Abdul Mutaleb Abas; Abdul Aziz Hairuddin; Mohd Khair Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Recently MRF damper -which has a significant controllable damping force - used frequently in many active and semi-active suspension systems. However, MRF damper needs controller to estimate the desired force to dissipate the occurred vibration instantaneously. PID controller is one of the effective feedback controllers which shows robustness and simplicity in control MRF dampers, but still the parameters of the PID controller under study to find out the optimum values. This study focused on the vibration control using Magneto-rheological (MR) damper on a FSAE quarter car suspension test rig to study and obtain the optimum running condition. The test rig was designed, modified and then tested using a P-controller integrated with MR damper, unbalance mass used as disturbance and analyzed using LABVIEW software in time and frequency domains. The natural frequency obtained was 2.2 Hz were similar to the actual FSAE car natural frequency. Based on the acceleration against time graph with different proportional gain value the optimal value for proportional gain, Kp was 1. Hence, the experiment work could be used as the initial stage to study and develop a robust controller to suppress vibration on a car.